Yield Responses to Planting Density for US Modern Corn Hybrids: A Synthesis‐Analysis. Issue 5 (1st September 2016) - Assefa, Yared; Vara Prasad, P. V.; Carter, Paul; Hinds, Mark; Bhalla, Gaurav; Schon, Ryan; Jeschke, Mark; Paszkiewicz, Steve; Ciampitti, Ignacio A.
Abstract : Identifying an optimal plant density is a critical management decision for corn ( Zea mays L.) production. The main objectives of this study were to: (i) investigate the grain yield responses to plant density (yield–density relationship), (ii) identify best fitted yield–density response curves, and (iii) explore genotype (G) × environment (E) interaction effect on yield–density response models. Analysis was conducted on meta‐data (124, 374 observations) gathered from 22 US states and 2 Canadian provinces, diverse sites (E), for years from 2000–2014 on multiple hybrids (G). Yield data were further grouped into four yield environments (low [LY], <7 Mg ha −1 ; medium [MY], 7–10 Mg ha −1 ; high [HY], 10–13 Mg ha −1 ; and very high [VHY], >13 Mg ha −1 yielding groups). Primary outcomes from this analysis were: (1) strong G × E interaction; (2) a quadratic model best fitted yield–density relationship; (3) four contrasting yield–density responses identified as dominant in each yield productivity environment, i.e., a declining, a constant, an increasing, and ever‐increasing type; (4) the yield productivity environment varied for the different corn comparative relative maturity (CRM) groups, i.e., the LY environment for long‐maturing hybrids matched with a MY or HY environment for short maturing hybrids; and (5) maximum yielding plant density (MYPD) was lower but maximum yield was greater for long‐ versus short‐maturing hybrids. In summary, optimal plant density should be decided based on detailed G × E analysis of production conditions that include factors such as CRM, yield productivity environment (weather–soil × management practices), and site information.